Detection of Escherichia coli bacteria by impact electrochemistry - Couto, R; Chen, L; Kuss, S; Compton, R (Royal Society of Chemistry, 2018)
We report the redox mediated detection of Escherichia coli bacteria at carbon microelectrodes, using the impact electrochemistry technique. By employing N,N,N’,N’-tetramethyl-para-phenylenediamine (TMPD) as redox mediator a concentration dependency for bacteria impacts was observed, whereby its impact frequency is shown to be in good agreement with theoretically predicted values.